Effect of interferon therapy on quality of life in patients with chronic hepatitis B - Mengdi Zhang; Meijuan Wan; Wen Wang; Shumei Lin; Xi Zhang (Scientific Reports, 2024)
Abstract Interferon therapy is the most effective treatment for achieving clinical cure in chronic hepatitis B (CHB) patients. However, the treatment outcomes of interferon therapy are uncertain, multiple side effects can occur during treatment, and the treatment is expensive. Although these characteristics may affect patients’ quality of life, research examining this topic is limited. We used a cross-sectional design to examine 100 CHB patients receiving interferon, 100 receiving nucleoside/nucleotide analogues, and 87 receiving non-antiviral treatment. Characteristic information, the Hepatitis B Quality of Life Instrument, Connor Davidson Resilience Scale, and Work Productivity and Activity Impairment Questionnaire were used to collect information. We found that quality of life in the interferon treatment group was higher than that in the non-antiviral treatment and nucleoside/nucleotide analogue treatment groups (p < 0.05). The factors influencing quality of life were resilience, presenteeism, hair loss, and antiviral treatment (p < 0.05). Although interferon therapy has some potential side effects, the results suggested that it did not negatively affect quality of life. Overall, interferon therapy did not have a major impact on CHB patients’ daily lives and work.